The European summer heatwave of 2019 – a regional storyline perspective - T. Klimiuk; P. Ludwig; A. Sanchez-Benitez; H. F. Goessling; P. Braesicke; P. Braesicke; J. G. Pinto (Earth System Dynamics)
The number and intensity of heatwaves have increased in the recent past, along with anthropogenic climate change. This poses challenges to many communities and emphasises the need to develop adaptation measures based on more accurate information regarding regional-to-local changes in temperature extremes and their impacts. While the general increase in global mean temperature is well established, current global climate projections show a large model spread concerning possible future circulation changes. To isolate the more certain thermodynamic response from the less certain dynamical response to anthropogenic climate change, we employ an event-based storyline approach and focus the present study on the 2019 summer heatwaves that occurred over central Europe. Our approach comprises three steps. Firstly, the large-scale circulation in the free troposphere was spectrally nudged to the ERA5 reanalyses within the global coupled climate model AWI-CM-1.1-MR for the recent period of 2017–2022, corresponding to global warming of +1.4 K. This process was then repeated under pre-industrial conditions, as well as under +2, +3, and +4 K global-warming climates. Secondly, the global storylines were dynamically downscaled using the regional ICOsahedral Nonhydrostatic model in Climate Limited-area Mode (ICON-CLM) to a EURO-CORDEX domain with a horizontal resolution of 12 km, and, thirdly, they were downscaled to a central European (German) domain with a resolution of 3 km. We provide evidence that the downscaling of global storyline integrations significantly improved the representation of present-day temperature patterns and reduced errors in daily 2 m temperatures relative to observations from central Europe. The magnitude of the heatwave temperature response significantly exceeds the globally modelled background warming, with distinct spatial and temporal variations in the regional increments. Our simulations indicate a general linear dependence of the 2 m temperature response on global-warming levels: during the July 2019 heatwave, warming rates ranged between factors of 2 and 3 in central Europe, resulting in anthropogenic warming of 8 to 12 °C in the +4 K climate. The spatial extent and duration of the heatwave are also amplified in the warmer climates. With this three-step downscaling approach, we gain new insights into possible future changes in heat extremes in central Europe, which apparently surpass global-warming trends. Along with its scientific value, our method provides ways to facilitate the communication of regional climate change information to users.